Biodegradable Cellulose Nanocomposite Substrate for Recyclable Flexible Printed Electronics. (29th January 2023) - Jaiswal, Aayush Kumar; Kumar, Vinay; Jansson, Elina; Huttunen, Olli‐Heikki; Yamamoto, Akio; Vikman, Minna; Khakalo, Alexey; Hiltunen, Jussi; Behfar, Mohammad H.
Abstract: Printed, flexible, and hybrid electronic technologies are advancing rapidly leading to remarkable developments in smart wearables, intelligent textiles, and health monitoring systems. Flexible electronics are typically fabricated on petroleum‐derived polymeric substrates. However, in the light of global environmental concerns regarding fossil raw materials, there is a need to drive the production of flexible electronics devices based on sustainable materials. Additionally, there is a need to reduce the quantity of electronic waste by developing material recovery and recycling technologies. Here, a fully biobased and biodegradable substrate tailored for printed flexible electronic applications is developed. Based on a nanocomposite of cellulose nanofibril (CNF) and hydroxyethyl cellulose (HEC), the substrate shows excellent mechanical and optical properties for printed flexible electronics applications. High‐resolution screen printing of conductive ink and typical electronics assembly processes are possible to realize on the substrate. An electrocardiograph (ECG) device is fabricated on the cellulosic substrate as a technology demonstrator and its performance is confirmed on human volunteers. Last, end‐of‐life scenarios are studied for printed electronic devices where device degradation and subsequent material recovery concepts are presented. This work demonstrates that sustainable plant‐derived materials can play a big role toward a green transition in the electronics industry. Abstract : This work demonstrates that sustainable plant‐derived materials can play a big role toward a green transition in the electronics industry. A biobased, biodegradable, and recyclable substrate for printed electronics is developed based on cellulose nanocomposite films. The substrate is flexible, transparent, conformal, printable, and allows simple recovery of materials at the end‐of‐life of electronic devices.